Reverse Migration, the Black Church and Sexual Health: Implications for Building HIV/AIDS Prevention Capacity in the Deep South - Foster, Pamela Payne (AIMS Public Health, 2016)
The Black Church has long been purported as being strongly influential in the lives of Blacks in America. Recent U.S. census data trends highlight a “reverse migration” pattern where Blacks are moving back to the South from larger metropolitan areas in other U.S. geographical regions. This migration pattern parallels the increasing HIV/AIDS prevalence among Blacks in the Deep South. This paper reviews both the historical and current migration patterns among Blacks, as well as the current HIV/AIDS epidemic among Blacks in the Deep South. Thereafter, the authors discuss an existing framework for increasing HIV/AIDS prevention capacity through a conceptual connection of migration, religion and sexual health. The authors use case studies to support the proposed framework. It is hoped that the framework could be used to address HIV/AIDS health disparities and other chronic diseases affecting Blacks in America.